Dezocine and butorphanol for the prevention of sufentanil-induced cough: a randomized controlled trial investigating the impact of intravenous access site - Liu, Ying; Ma, Hong-Yan; Shi, Jing-Hui (Frontiers in Pharmacology, 2026)
IntroductionSufentanil, a potent opioid commonly used for anesthesia induction, is frequently associated with a cough reflex that may compromise airway stability and elevate intracranial or intraocular pressure. While pretreatment with opioids such as dezocine or butorphanol has been proposed to mitigate this reaction, comparative data on their efficacy are limited. This study aimed to primarily evaluate and compare the effects of dezocine and butorphanol in preventing sufentanil-induced cough (SIC), and secondarily, to investigate the impact of intravenous access site (hand vs. foot) on SIC incidence and severity during general anesthesia induction.MethodsIn this randomized controlled trial, 246 ASA I–II patients (aged 18–65) scheduled for elective surgery were assigned to six groups (n = 41 each) using a random number table. Group Ia/Ib received dezocine 0.1 mg/kg via hand/foot venous access; Group IIa/IIb received butorphanol 0.02 mg/kg via hand/foot access; Group IIIa/IIIb received 5 mL normal saline via hand/foot access. All study drugs were diluted to 5 mL and administered intravenously, followed 3 min later by sufentanil 0.5 μg/kg given over 3 s. The incidence, severity (graded 1–3), and onset time (within 1 min) of SIC were recorded.ResultsSIC incidence was 1.25% in the dezocine group, 0% in the butorphanol group, and 38.75% in the saline group. Both dezocine and butorphanol significantly reduced SIC incidence compared to saline (P < 0.05), with no significant difference between the two active drugs. Among saline subgroups, SIC incidence was significantly higher with hand venous access (52.5%) compared to foot access (25%) (P < 0.05), accompanied by faster onset and greater severity in the hand-access group (P < 0.05). The site of intravenous access significantly influences SIC, with foot venous access markedly reducing its incidence and severity compared to hand access. Furthermore, both dezocine and butorphanol are highly effective in suppressing SIC, with comparable efficacy between them.DiscussionThese findings establish the optimization of intravenous access site as a simple, nonpharmacological strategy for SIC prophylaxis, which can be used alone or in conjunction with pharmacologic pretreatment.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=24109, identifier, ChiCTR-IPR-17014201.